2019
DOI: 10.1186/s40834-019-0085-1
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal child spacing practice and its associated factors among women of child bearing age in Serbo town, JIMMA zone, Southwest Ethiopia

Abstract: Introduction Birth spacing is the time gaps between two consecutive life births. Optimal spacing until the next pregnancy is the resting period that allows the mother time to recover from pregnancy, and labor. Birth interval of 3 to 5 years increases maternal health and child survival and family planning programs have advocated this birth interval. Objectives To assess prevalence of Suboptimal Child spacing practice and its associated factors among Women of Child bearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 8 publications
6
32
2
Order By: Relevance
“…From the 9 articles, 6 studies with a total of 3,797 women of childbearing age were included to estimate the pooled prevalence of short birth spacing in Ethiopia. The lowest prevalence of short birth spacing (23.3%) was reported from a study done in the Tselemti district, Tigray region [ 40 ] whereas the highest prevalence of short birth spacing (59.9%) was observed from a study done in Serbo town, Oromia region [ 39 ]. ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 9 articles, 6 studies with a total of 3,797 women of childbearing age were included to estimate the pooled prevalence of short birth spacing in Ethiopia. The lowest prevalence of short birth spacing (23.3%) was reported from a study done in the Tselemti district, Tigray region [ 40 ] whereas the highest prevalence of short birth spacing (59.9%) was observed from a study done in Serbo town, Oromia region [ 39 ]. ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of three studies [ 39 , 42 , 43 ] were included to identify the association between the duration of breastfeeding and short birth spacing. The result of the random-effect meta-analysis showed the odds of practicing short birth spacing was 16.9 higher among women who breastfeed their child less than 24 months as compared to women who breastfeed ≥ 24 months [OR = 16.9, 95%CI: (2.69, 106.47)].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size of included studies was ranged from 7740 for the National Ethiopian Demographic Health Survey in the crossectional study from Ethiopia [16] to 314 Serbo Town [17] (table 1). Out of 13 studies included in the meta-analysis, 16311 women were involved.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…(Table 1). From thirteen studies, Ten of them were showed a statistically significant association between contraceptive use and short of birth interval [17][18][19][20][23][24][25][26][27][28] while, three studies did not showed a statistically significant association between contraceptive use and short of birth interval [16,21,22].…”
Section: Study Characteristicsmentioning
confidence: 99%